The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4172/2375-446x.1000132
|View full text |Cite
|
Sign up to set email alerts
|

The High Cost of Pesticides: Human and Animal Diseases

Abstract: A significant degradation in the health of wild animals in Montana has been recorded over the past two decades. We surmise that the health issues are related to pesticide exposure. We present some of the evidence of the deterioration of the health in wildlife, which we used to inspire investigations on human health in the US population. While the animals' exposure is through food, water and air, we believe that human exposure is predominantly through food, as the majority of the population does not reside near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 91 publications
(109 reference statements)
0
11
0
2
Order By: Relevance
“…These include obesity, diabetes, end stage renal disease, renal failure, autism, Alzheimer's disease, dementia, Parkinson's disease, multiple sclerosis, intestinal infection, inflammatory bowel disease, stroke, leukemia, thyroid cancer, liver cancer, bladder cancer, pancreatic cancer and kidney cancer. Another study, looking at both human and animal data, revealed a large number of disorders of the newborn that are increasing in step with glyphosate usage [31]. These include congenital heart disease, skin disorders, genitourinary disorders, blood disorders, metabolic disorders and lung conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These include obesity, diabetes, end stage renal disease, renal failure, autism, Alzheimer's disease, dementia, Parkinson's disease, multiple sclerosis, intestinal infection, inflammatory bowel disease, stroke, leukemia, thyroid cancer, liver cancer, bladder cancer, pancreatic cancer and kidney cancer. Another study, looking at both human and animal data, revealed a large number of disorders of the newborn that are increasing in step with glyphosate usage [31]. These include congenital heart disease, skin disorders, genitourinary disorders, blood disorders, metabolic disorders and lung conditions.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the results of work on other wild ungulates indicates significant evidence of the adverse effect of pesticides [21]. This includes the under development of the upper facial bones brachygnathia superior found to affect, inter alia, white-tailed deer Odocoileus virginianus, mule deer Odocoileus hemionus, elk Cervus canadensis, pronghorn antelope Antilocapra americana and bighorn sheep Ovis canadensis [21,22]. These populations were found to suffer from congenital urogenital malformations [23,24] such as a decrease in penis sheath length, scrotum size, and the change in testes position.…”
Section: Introductionmentioning
confidence: 99%
“…The issue of the impact of pesticides on European bison has not been studied so far. At the same time, the results of work on other wild ungulates indicates significant evidence of the adverse effect of pesticides [21]. This includes the under development of the upper facial bones brachygnathia superior found to affect, inter alia, white-tailed deer Odocoileus virginianus, mule deer Odocoileus hemionus, elk Cervus canadensis, pronghorn antelope Antilocapra americana and bighorn sheep Ovis canadensis [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a paper published in 2014, Swanson et al showed a remarkable correlation between the rising rate of glyphosate usage on corn (maize) and soy crops in the USA and an alarming rise in a number of different chronic diseases [24]. Additional strong correlations for other conditions and diseases are provided in two follow-on papers [25,26]. While correlation does not necessarily mean causation, causation becomes much more likely if a plausible mechanism can be found.…”
Section: Introductionmentioning
confidence: 99%